2010
DOI: 10.3109/02841850903307566
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of articular cartilage abnormalities of the far posterior femoral condyle of the knee

Abstract: Articular cartilage abnormalities of the FPFC are common and were demonstrated in 24% of patients or 30% of cases. Lateral FPFC abnormalities occur 2.5 times more frequently than medial FPFC abnormalities and were more frequently focal compared with medial cohorts. BME is associated in 36.5% of cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…due to the different mechanical constraints sustained by the two condyles. 19,20 In fact, studies have found a high frequency of cartilage lesions at the posterior aspect of the lateral condyle (up to 24% of 654 consecutive knee MRIs), while in the great majority of cases, cartilage is preserved at the most posterior aspect of the medial condyle until the latest stages of OA (up to 87% of 41 consecutive pre-total knee arthroplasty knees). 19,20 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…due to the different mechanical constraints sustained by the two condyles. 19,20 In fact, studies have found a high frequency of cartilage lesions at the posterior aspect of the lateral condyle (up to 24% of 654 consecutive knee MRIs), while in the great majority of cases, cartilage is preserved at the most posterior aspect of the medial condyle until the latest stages of OA (up to 87% of 41 consecutive pre-total knee arthroplasty knees). 19,20 This study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 In fact, studies have found a high frequency of cartilage lesions at the posterior aspect of the lateral condyle (up to 24% of 654 consecutive knee MRIs), while in the great majority of cases, cartilage is preserved at the most posterior aspect of the medial condyle until the latest stages of OA (up to 87% of 41 consecutive pre-total knee arthroplasty knees). 19,20 This study has several limitations. First, although most potential confounders that have been previously described to correlate with cartilage thickness, including age, gender and bone size, were not different between the non-OA and OA groups, other parameters related to the physical size of the participants (such as height, weight and body mass index) were not analyzed as these data were unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…These areas of irregular ossifi cation can be confused with subchondral bone fragments, as seen with osteochondritis dissecans ( 16 ). The lack of adjacent bone marrow edema in the epiphysis and the more posterior location on sagittal MR images indicate that this variation in ossifi cation represents normal development ( 10,17 ). In our study, extra ossifi cation centers were a rare (in nine [1.0%] patients) ossifi cation variability.…”
Section: Pediatric Imaging: Mr Imaging Of Condylar Ossifi Cation Varimentioning
confidence: 46%
“…One study found ACL-rupture patients had an increased risk for OA pathological features [18,30]. Focal cartilage abnormalities of the far posterior articular cartilage were seen 2.5 times more frequently in the lateral femoral condyle compared to the medial femoral condyle [36]. One of these pathological features has been studied thoroughly due to its prevalence.…”
Section: Osteoarthritismentioning
confidence: 99%
“…A very MRI-specific artifact is what is known as the "magic-angle effect". This artifact is associated with tissues oriented at 54.44° to the B0 magnetic fields, and higher intensities may be artificially encountered when using short echo time techniques, like protondensity, T1-weighted, and T2 mapping sequences [23,28,36]. This is due to collagen alignment's effect on the efficiency of the T2 dipole interactions, which manifests in vertical striations within the cartilage image [43].…”
Section: The Basic Physics Of Mr Imagingmentioning
confidence: 99%